Organization Culture and Open Innovation in Sustainable Agri-business: A Case Study of Jain Irrigation Systems Limited - Bhadauria, Shraddha; Singh, Vinay (The journal of contemporary issues in business and government, 2021)
Purpose – The purpose of the paper is to exploring linkages among organization culture, open innovation and sustainable business framework in the context of agri-business based firm. Design/methodology – A conceptual model and theoretical framework based on competency value has been established through exhaustive literature review and verified through secondary data obtained from the report published by an agro-business firm on the continuum of annual basis followed by structured qualitative interview of the experts indulged in concerned industry. Findings – The qualitative analysis demonstrates competency value framework for case- organization gaining sustainable business with the aid of open innovation. Research findings suggest that case company incorporate product innovation, process innovation in the adhocracy culture. Moreover, the firm accomplishes continued growth through sustained open innovation leading to customer satisfaction and sustainable business. Also, it is able to meet fair return to all other stakeholders withholding corporate philosophy of being transparent, farmers oriented, and market leader. Their results can be valuable to other companies. Research limitations/implications – The limitation of the study resides in its general applicability. Like other case studies, the specific conditions obtained in one organization may not be found more generally in a different organization of the industry segment generally due to varying leading strategic orientation of individual firms. Thus the results of the study may have applicability to other firms falling in same industry segment and meeting with almost similar circumstances. Originality/value – The paper explains the linkage and impact of cultural dimensions on sustained innovation directed towards complete customer satisfaction, quality excellence and finally leads to sustainable business growth of a firm.